Faktor yang Berhubungan dengan Perilaku Ibu Menyusui dalam Pemanfaatan Pangan Lokal Sumber Probiotik - Suci Rahmani Nurita; Tuhu Perwitasari; Ova Jayanti; Ratu Kusuma; Nurbaiti Nurbaiti (Jurnal Akademika Baiturrahim Jambi, 2026)
One effort to maintain digestive health is to consume foods containing probiotics obtained from local foods, namely fermented foods such as tempeh, pickles, tempoyak, tauco and tape. Probiotics that breastfeeding mothers get from daily consumption of local food are good for the health of the mother's digestive tract and their babies from breastfeeding. The total lactic acid bacteria in breast milk is between 5,000 – 46,000 CFU/ml, it is estimated that a baby every day obtains around 500 thousand to 5 million lactic acid bacteria cells. This study aims to determine the behavior of breastfeeding mothers in utilizing local food sources probiotics. This research method is an analytic survey with a cross sectional design. The population of this study were all breastfeeding mothers who had babies aged 0-2 years at PMB Muzilatul Nisma with a total sample of 10 people using accidental sampling technique. The research was conducted from December 2022 to July 2023 using an e-questionnaire. Data were analyzed using the Chi-Square test. The results showed that there was no relationship between knowledge, attitudes and perceptions of breastfeeding mothers regarding the use of local food sources of probiotics (p value 0.491; 0.576; 0491). There is a relationship between food taboos for breastfeeding mothers regarding the use of local food sources of probiotics (p value = 0.024). It would be better if midwives could increase education regarding local food sources of probiotics and breastfeeding mothers could increase their knowledge and utilization of probiotic sources from local food.